High-resolution proteomic and lipidomic analysis of exosomes and microvesicles from different cell sources. Issue 1 (1st January 2016) - Haraszti, Reka A.; Didiot, Marie-Cecile; Sapp, Ellen; Leszyk, John; Shaffer, Scott A.; Rockwell, Hannah E.; Gao, Fei; Narain, Niven R.; DiFiglia, Marian; Kiebish, Michael A.; Aronin, Neil; Khvorova, Anastasia
Abstract : Extracellular vesicles (EVs), including exosomes and microvesicles (MVs), are explored for use in diagnostics, therapeutics and drug delivery. However, little is known about the relationship of protein and lipid composition of EVs and their source cells. Here, we report high-resolution lipidomic and proteomic analyses of exosomes and MVs derived by differential ultracentrifugation from 3 different cell types: U87 glioblastoma cells, Huh7 hepatocellular carcinoma cells and human bone marrow-derived mesenchymal stem cells (MSCs). We identified 3, 532 proteins and 1, 961 lipid species in the screen. Exosomes differed from MVs in several different areas: (a) The protein patterns of exosomes were more likely different from their cells of origin than were the protein patterns of MVs; (b) The proteomes of U87 and Huh7 exosomes were similar to each other but different from the proteomes of MSC exosomes, whereas the lipidomes of Huh7 and MSC exosomes were similar to each other but different from the lipidomes of U87 exosomes; (c) exosomes exhibited proteins of extracellular matrix, heparin-binding, receptors, immune response and cell adhesion functions, whereas MVs were enriched in endoplasmic reticulum, proteasome and mitochondrial proteins. Exosomes and MVs also differed in their types of lipid contents. Enrichment in glycolipids and free fatty acids characterized exosomes, whereas enrichment in ceramides and sphingomyelins characterized MVs. Furthermore, Huh7 and MSC exosomes were specifically enriched in cardiolipins; U87 exosomes were enriched in sphingomyelins. This study comprehensively analyses the protein and lipid composition of exosomes, MVs and source cells in 3 different cell types.